Health policy, power and politics : sociological insights - Calnan, Michael (Emerald Group Publishing Limited, 2020)
In the context of substantial changes in health service policy and public health policy in England and Wales over the last two decades, Health Policy, Power and Politics fills an important gap by providing an up-to-date and accessible account and sociological analysis of recent trends in health policies.